High resolution functional photoacoustic tomography of breast cancer. Issue 9 (18th August 2015) - Li, Xiaoqi; Heldermon, Coy D.; Yao, Lei; Xi, Lei; Jiang, Huabei
Abstract : Purpose: To evaluate the feasibility of functional photoacoustic tomography (fPAT) for high resolution detection and characterization of breast cancer and to demonstrate for the first time quantitative hemoglobin concentration and oxygen saturation images of breasts that were formed with model‐based reconstruction of tomographic photoacoustic data. Methods: The study was HIPAA compliant and was approved by the university institutional review board. Written informed consents were obtained from all the participants. Ten cases, including six cancer and four healthy (mean age = 50 yr; age range = 41–66 yr), were examined. Functional images of breast tissue including absolute total hemoglobin concentration (HbT ) and oxygen saturation (StO2 %) were obtained by fPAT and cross validated with magnetic resonance imaging (MRI) readings and/or histopathology. Results: HbT and StO2 % maps from all six pathology‐confirmed cancer cases (60%) show clear detection of tumor, while MR images indicate clear detection of tumor for five of six cancer cases; one small tumor was read as near‐complete‐resolution by MRI. The average HbT and StO2 % value of suspicious lesion area for the cancer cases was 61.6 ± 18.9 μ M/l and 67.5% ± 5.2% compared to 25.6 ± 7.4 μ M/l and 65.2% ± 3.8% for background normal tissue. Conclusions: fPAT has the potential to be a significant add‐on in breast cancer detection and characterization as it provides submillimeter resolution functional images of breast lesions.